2011
DOI: 10.1002/stem.767
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Remyelination by Neural Stem/Progenitor Cells Transplanted into the Injured Spinal Cord

Abstract: Previous reports of functional recovery from spinal cord injury (SCI) in rodents and monkeys after the delayed transplantation of neural stem/progenitor cells (NS/PCs) have raised hopes that stem cell therapy could be used to treat SCI in humans. More research is needed, however, to understand the mechanism of functional recovery. Oligodendrocytes derived from grafted NS/PCs remyelinate spared axons in the injured spinal cord. Here, we studied the extent of this remyelination's contribution to functional recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
117
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 74 publications
9
117
0
Order By: Relevance
“…Previous studies have demonstrated that NS/PC transplantation for SCI affects histological and/or functional outcomes in several processes, including neurotrophic support [32,33], angiogenesis [34,35], axonal regrowth [24,36], neural circuit reconstruction [37][38][39], and remyelination [40,41]. Most of these previous studies involved the use of rodent SCI models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that NS/PC transplantation for SCI affects histological and/or functional outcomes in several processes, including neurotrophic support [32,33], angiogenesis [34,35], axonal regrowth [24,36], neural circuit reconstruction [37][38][39], and remyelination [40,41]. Most of these previous studies involved the use of rodent SCI models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, remyelination is one of the potential mechanisms for functional recovery, especially at the late phase after NS/PC transplantation [40,41,57,58]. However, it is difficult to obtain oligodendrocytes derived from human NS/PCs [12] and human iPSC-NS/PCs [33] in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies [25][26][27][28][29][30] , we found that transplanted neural stem cells (NSCs) survived and differentiated into neurons, astrocytes, and oligodendrocytes, which are three major cellular components of the CNS. Graft-derived neurons formed synapses with host neurons and integrated with host neuronal circuits.…”
mentioning
confidence: 99%
“…Graft-derived neurons formed synapses with host neurons and integrated with host neuronal circuits. Graft-derived oligodendrocytes were shown to participate in re-myelination of host axons in SCI models [ 28,30 ] , which signi fi cantly contributes to functional recovery after SCI [ 30 ] . It is possible that graft-derived astrocytes and undifferentiated NSCs produce various trophic factors that support angiogenesis [27][28][29] , cellular survival, and axonal regeneration of host axons including 5-HT-positive raphe-spinal tracts involved in the locomotive functions of hindlimbs [27][28][29] .…”
mentioning
confidence: 99%